Book review: Access audit in religious building and public spaces in Old Damascus City Syria - Abdul Rahim, Asiah (Kulliyyah of Architecture & Environmental Design, International Islamic University Malaysia, 2012)
The significant of this book edited by Asiah Abdul Rahim presents title Access audit in religious buildings and public spaces in Old Damascus City Syria. The book was published in 2012 with five (5) chapters of an inclusive of four (4) case study building, authored by Ismawi Zen, Asiah Abdul Rahim, Aniza Abu Bakar and Fadzidah Abdullah. Heritage buildings in the Islamic Era have been known due to its significant contribution and heritage trails of previous Islamic rulers of its time. The typology of these heritage buildings are according to function and usage but most of it are consider public building that accommodates the livelihood of traders and merchants during the trades era. Damascus is the capital of the first Islamic empire namely the Umayyad after the seat of government was moved Madinah al Munawarah.